Toward Understanding the Evolutionary Role of Star-forming Lenticular Galaxies: New H i Detections and Comparison with Quiescent S0s and Red Spirals - Pei-Bin Chen; Junfeng Wang; Tian-Wen Cao; Mengting Shen; Xiaoyu Xu (The Astrophysical Journal)
As one type of blue early-type galaxy, the evolutionary history and fate of star-forming lenticular galaxies (S0s) remain elusive. We selected 134 star-forming S0s from the Sloan Digital Sky Survey IV MaNGA survey and found that they have steep and warped size–mass relations, similar to quiescent S0s and red spirals, indicating that they may have similar gas dissipation scenarios. These galaxies have a higher central stellar mass surface density than normal blue spirals. The radial profiles of D _n 4000 and [Mgb/Fe] show that red spirals and quiescent S0s have similar old central populations and high [Mgb/Fe] values, suggesting rapid bulge formation, though red spirals exhibit a steeper gradient possibly due to residual star formation (SF) in outer regions. In contrast, star-forming S0s exhibit profiles between quiescent S0s/red spirals and normal blue spirals, with relatively flat D _n 4000 and [Mgb/Fe] gradients. More long-term SF history causes normal blue spirals to have very flat D _n 4000 and [Mgb/Fe] profiles, and the majority of them (79% ± 5%) have a Sérsic index of <2. We also found that the halo mass of star-forming S0s resembles that of quiescent S0s/red spirals, with 82% ± 5% exceeding the critical mass ( M _halo = 10 ^12 M _⊙ h ^−1 ). To supplement previous H i detection of star-forming S0s covered by H i MaNGA, we obtained new observations for H i emission from 41 star-forming S0s in our sample using the Five-hundred-meter Aperture Spherical Radio Telescope. We found that the H i mass distribution of star-forming S0s matches that of normal blue spirals, although both star-forming S0s and red spirals are relatively gas-poor, resulting in varying atomic gas depletion times due to different SF levels. Based on these observational results, we discuss the possible evolutionary scenarios of star-forming S0s.